2014
DOI: 10.1371/journal.pone.0111887
|View full text |Cite
|
Sign up to set email alerts
|

Exonic Variants Associated with Development of Aspirin Exacerbated Respiratory Diseases

Abstract: Aspirin-exacerbated respiratory disease (AERD) is one phenotype of asthma, often occurring in the form of a severe and sudden attack. Due to the time-consuming nature and difficulty of oral aspirin challenge (OAC) for AERD diagnosis, non-invasive biomarkers have been sought. The aim of this study was to identify AERD-associated exonic SNPs and examine the diagnostic potential of a combination of these candidate SNPs to predict AERD. DNA from 165 AERD patients, 397 subjects with aspirin-tolerant asthma (ATA), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…In this sense, a recent genome-wide methylation study on nasal polyps found a differential pattern in patients with NSAID-induced DHRs [133], and a set of 2 gene markers has been proposed to discriminate NERD from aspirin-tolerant asthma [134]. Exome sequencing has also been used to identify variants associated with hypersensitivity to NSAIDs [135].…”
Section: Further Approaches For Deciphering Dhrsmentioning
confidence: 99%
“…In this sense, a recent genome-wide methylation study on nasal polyps found a differential pattern in patients with NSAID-induced DHRs [133], and a set of 2 gene markers has been proposed to discriminate NERD from aspirin-tolerant asthma [134]. Exome sequencing has also been used to identify variants associated with hypersensitivity to NSAIDs [135].…”
Section: Further Approaches For Deciphering Dhrsmentioning
confidence: 99%
“…Three additional exonic SNPs on HLA-DPB1 (exm537513, exm537522 and exm537523) were also present among the top 20 SNPs. A prior GWAS 77 had identified exm537522 (also annotated as rs1042151 in that study) as having the strongest association with AERD susceptibility; therefore, the authors replicated one of their top associations from a previous study 76 . To develop a predictive model for AERD risk, the authors selected the best combination of the top 10 SNPs that could discriminate between AERD and ATA, using multiple logistic regression, and calculated ROC curves and AUC values for each combination model 76 .…”
Section: Update On the Genetics Of Aerdmentioning
confidence: 65%
“…Shin et al recently used an exome-wide profiling approach using the HumanExome BeadChip v1.1 (Illumina Inc.) to identify novel, rare and exonic SNPs associated with AERD status in 165 AERD patients, 397 patients with ATA, and 398 normal controls of Korean ancestry 76 . After filtering and quality control of genotype data, over 54,000 SNPs remained and were evaluated for association with AERD risk 76 . A SNP in HLA-DPB1 , exm537513, achieved genome-wide significance and was associated with increased risk of AERD (OR: 3.28, p -value of 3.4×10 −8 ) 76 .…”
Section: Update On the Genetics Of Aerdmentioning
confidence: 99%
See 2 more Smart Citations